Controlled fermentation, honey, bees and alcohol: archaeological and ethnohistorical evidence from southern Africa - Rusch, Neil (Southern African Humanities, 2020)
In this paper I present the results of a fermentation experiment in which alcohol is produced by combining honey, water and moerwortel (Glia prolifera). The procedure and combination of ingredients follows an indigenous method, as was conveyed to the botanist Carl Thunberg by KhoeSan informants in the 18th century. Results of this experiment are contextualized using ethnohistorical and early traveller testimonies that suggest widespread use of honey-alcohol combined with plant material for psychotropic and medicinal purposes. This included kanna (Sceletium tortuosum), which produced a ‘spiked’ honey drink known as khadi. Controlled fermentation may have emerged as early as the MSA, together with manifestations of complex behaviour and mental processing that was cognisant and capable of using a suite of complementary botanical, technical and chemical methods for various applications, such as making arrow poison and the synthesis of compound materials for the manufacture of mastics, adhesives and pigment. An explanatory framework encompassing an MSA and deep-time perspective helps to explain the related themes of honey bees in southern San mythology, pictorial expression and fermentation practices. KEY WORDS: Honey, fermentation, KhoeSan, bow and arrows, poison, cognitive modernity.